Weapon, Lure and Object of Desire: Gendered Ideology in Lipstick Advertising - Papadima, Aspasia (My University, 2022)
Advertising as a means of information, promotion and persuasion contributes to the construction of lifestyle trends, shaping social stances and establishing sociocultural ideologies. Cosmetics advertising, which has been prolific since its beginnings in the mid-19th century, highlights the clear interrelation between advertising and culture. In this context, the cosmetics industry’s best-selling product – since its commercially successful debut – is the lipstick; acknowledging its promising selling potential, lipstick manufacturers have invested systematically in its promotion. The advertising industry continues to dynamically propel lipstick marketing, resulting in a plethora of print adverts that have been thriving in women’s magazines over the years. Focusing on lipstick as a case study in advertising, while drawing references from feminist history and with the aid of semiotic analysis on the design of lipstick adverts, this study aims to a) review significant milestones in the promotion of lipstick through advertising; b) highlight socially constructed stereotypes of female behaviour, such as being dutiful and subservient, or scheming, lustful and narcissistic; and c) unveil the gendered ideology implicit in both visual and oral advertising messages. Finally, the study discusses the shift in mindset driven by third wave feminism, as illustrated by Gucci’s 2019 lipstick advertising campaign.
Keywords: Lipstick; Advertising; Semiotic analysis; Gender stereotypes; Gucci lipstick campaign